PENGARUH PYRACLOSTROBIN PADA PEMBENTUKAN BUAH KOPI ROBUSTA (Coffea canephora) - Wiharyanti Nur Lailiya; Karuniawan Puji Wicaksono; Eko Widaryanto (Universitas Tribhuwana Tunggadewi, 2018)
Robusta coffee (Coffea canephora) is one of the commodities that have high economic value among other plantation crops. Coffee is also one of the three non-alcoholic beverages (coffee, tea, chocolate) are widespread. Indonesia and among the countries located in the international coffee world, because Indonesia is the third largest coffee exporter after Brazil and Vietnam. Coffee production in Indonesia reached an average of 11.250 tonnes per year. The purpose of this study is studying the ability of pyraclostrobin on coffee fertilization, thereby reducing the occurrence of fruit drop and determining the appropriate concentrations for spraying treatment pyraclostrobin on fertilization and reduce fruit drop robusta coffee. This study was conducted in January-September 2016 in the coffee plantation Tlogosari, Tirtoyudo subdistrict, Malang regency which is located at the altitude of 560 m above sea level. The method that used in this study is a randomized block design, consisting of 6 treatments and 4 replications. While the treatment is P0 (without spraying), P1 (Spraying once a week with a concentration of 150 ppm), P2 (Spraying once a week with a concentration of 300 ppm), P3 (Spraying once a week with a concentration of 450 ppm), P4 (Spraying once a week with a concentration of 600 ppm), P5 (Spraying once a week with a concentration of 750 ppm). Giving pyraclostrobin with a concentration of 600 ppm may increase the amount of fruit compared to the treatment without giving pyraclostrobin.